Theoretical and experimental investigation of the behaviour of ultrasound contrast agent particles in whole blood. - Stride, E; Saffari, N (2004)
The majority of the existing models for the behaviour of ultrasound (US) contrast agents consider a single contrast agent particle (CAP) surrounded by an infinite, homogeneous and Newtonian fluid. In vivo, however, CAPs are suspended within the confines of blood vessels, in fluid containing both other CAPs and a high volume fraction of cells of comparable size. The aim of this work was to investigate the influence of blood cells upon CAP acoustic response to determine how existing models should be modified for the purposes of improving CAP design. A new model for a CAP surrounded by a cluster of cells was derived and solved numerically. Broadband US attenuation measurements were then made in suspensions of Optison (Amersham PLC, Bucks, UK) in plasma and in whole blood. Both the theoretical and experimental results indicate that the presence of blood cells has a relatively small effect upon CAP dynamics and hence acoustic response. This implies that it is justifiable to model blood as homogeneous and Newtonian for the purposes of CAP design.